A novel approach to enhance beta-sitosterol bioavailability isolated from Jurinea macrocephala (a high-altitude) plant in biodegradable chitosan against lung cancer - Sangral, Monica; Singh, Ankita; Gupta, Ashutosh; Bhagat, Madhulika (Frontiers in Oncology, 2025)
IntroductionLung cancer remains a significant health challenge, often resulting in a poor prognosis due to the limited availability of effective targeted therapies. Beta-sitosterol (BS), extracted from Jurinea macrocephala, possesses diverse pharmacological properties but faces limitations such as poor solubility and low bioavailability. This study aims to address these limitations by encapsulating β-sitosterol in chitosan nanoparticles, thereby enhancing its solubility and controlled and sustained release to improve therapeutic efficacy against lung cancer with an emphasis on exploring its potential mode of cell death.MethodsBS was isolated using column chromatography, with high-performance liquid chromatography (HPLC) confirming its purity. The ionic crosslinking method with tripolyphosphate (TPP) was employed to formulate chitosan-based nano beta-sitosterol (BSC). The characterization of the nanoparticles was performed using field emission scanning electron microscopy (FE-SEM), dynamic light scattering (DLS), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR). Cell-based assays, including 4′,6-diamidino-2-phenylindole (DAPI) staining, colony formation, apoptosis, and cell cycle analysis, were conducted to assess the effects of nano β-sitosterol compared to its pure form on A549 lung cancer cell lines.Resultsβ-Sitosterol (0.6% w/w) was isolated from J. macrocephala chloroform extract collected from the Bhaderwah region of Jammu and Kashmir. The resulting nanoparticles had an average size of 190 nm, a polydispersity index of 0.592, and a zeta potential of 16.3 mV. The nanoparticles displayed encapsulation efficiency of 76% ± 2.19% with a loading capacity of 3.04 ± 2.08. In vitro release studies have demonstrated a sustained release of β-sitosterol over 7 days. Cell-based assays indicated that nano β-sitosterol had a more prolonged and controlled effect on cell proliferation, nuclear distortion, cell cycle progression, and apoptosis in A549 cells compared to free β-sitosterol. This study is the first to compare the effects of nano β-sitosterol versus pure β-sitosterol on apoptosis and cell cycle progression in a time-dependent manner.DiscussionChitosan-encapsulated nano β-sitosterol demonstrated enhanced solubility, sustained release, and improved therapeutic efficacy against lung cancer, highlighting its potential as a promising delivery system for lung cancer with improved therapeutic outcomes.